2022
DOI: 10.15537/smj.2022.43.1.20210733
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hematological parameters in dyspepsia patients infected with Helicobacter pylori

Abstract: The data of dyspepsia and epigastric pain patients were derived from the hospital based registration system between 2020-2021. Logistic regression models were used to investigate the correlation between the onset of H. pylori infection and anemia.Results: Among 810 enrolled patients, there were 202 )24.9%( patients with H. pylori infection and 144 )17.8%( with anemia. The prevalence of anemia in the H. pylori )+( group was not statistically higher than the H. pylori )-( group after adjusting age, red blood cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…However, the virulent oncoprotein CagA was found significantly correlated to both vitamin B12 and ferritin deficiencies. Several literature reviews have shown controversial studies related to H. pylori , ferritin and vitamin B12 deficiencies [ [40] , [41] , [42] , [44] , [45] , [46] , [47] , [48] , [91] , [92] , [93] , [94] ] while few studies have explored the correlation between the oncoprotein CagA and ferritin, vitamin B12 deficiencies [ 43 , 95 ]. In the current study, the association between H. pylori , CagA, ferritin and vitamin B12 in the UAE population was investigated for the first time on a large scale.…”
Section: Discussionmentioning
confidence: 99%
“…However, the virulent oncoprotein CagA was found significantly correlated to both vitamin B12 and ferritin deficiencies. Several literature reviews have shown controversial studies related to H. pylori , ferritin and vitamin B12 deficiencies [ [40] , [41] , [42] , [44] , [45] , [46] , [47] , [48] , [91] , [92] , [93] , [94] ] while few studies have explored the correlation between the oncoprotein CagA and ferritin, vitamin B12 deficiencies [ 43 , 95 ]. In the current study, the association between H. pylori , CagA, ferritin and vitamin B12 in the UAE population was investigated for the first time on a large scale.…”
Section: Discussionmentioning
confidence: 99%